STAKEHOLDER POWER ANALISYSIS UNTUK MEMPREDIKSI KUALITAS PENGUNGKAPAN SUSTAINABILITY REPORT (Studi Empiris Pada Perusahaan Peserta Asia Sustainability Reporting Rating Tahun 2019) - Ade Adriani; Maria Chatarina Maharani Putri Mahayana (Universitas Lambung Mangkurat, 2021)
This research aims to obtain evidence of the effect of stakeholders’ pressure, such as pressure from consumer, shareholder, creditor, employee, government, mass media, and community and environmental activist toward the quality of company’s sustainability report disclosure in Indonesia. The population in this research were the Indonesian companies that join to be participants in Asia Sustainability Reporting Rating (ASRRAT) 2019. This research used the purposive sampling method. Data were analyzed by ordinal logistic regression using IBM SPSS 24. The result showed that the pressure from community and environmental activist improves the quality of sustainability report disclosure. It means that higher the pressure from consumer, community and environmental activist to company will increase the quality of sustainability reporting disclosure. On other hand, the pressure from shareholder, creditor, employee, government and mass media to quality of company’s sustainability report disclosure influence with a lower level of confidence. Stakeholder pressure affects the quality of sustainability report disclosure by 44,6%, while 55,4% level of quality can be influenced by other factors